Augmenter of Liver Regeneration Crotonylation Assists in Mitochondria-ER Contact to Alleviate Hepatic SteatosisSummary - Xiao-lin Wang; Jia-hao He; Ping Xie; Yuan Wu; Ling-yue Dong; Wei An (Cellular and Molecular Gastroenterology and Hepatology)
Background & Aims: Crotonylation (Kcr), a newly identified post-translation modification (PTM), has been confirmed to be involved in diverse biological processes and human diseases as well. Metabolic dysfunction-associated steatotic liver disease (MASLD) poses a serious threat to people’s health. Augmenter of liver regeneration (ALR) is an important liver regulatory protein, and the insufficiency of ALR expression is reported to accelerate liver steatosis progression to liver fibrosis or even hepatic carcinoma (HCC). However, the connection between dysregulated ALR crotonylation and MASLD pathogenesis remains largely unknown. Methods: Steatotic liver samples from human and Western diet (WD)-fed mice were employed for detecting Kcr levels. Mitochondrial function and mitochondria-ER interaction (MAM) relevant to ALR-Kcr modification was evaluated for hepatocyte lipid metabolism both in in vivo and in vitro experiments. Results: Global protein crotonylation (Kcr) as well as ALR-Kcr was significantly decreased in liver samples of patients with MASLD and WD mice. Histone deacetylase1/2 (HDAC1/2) and lysine acetyltransferase 8 (KAT8) were identified responsible for regulation of ALR-Kcr, which takes place at lysine 78 (K78). The decrease of ALR crotonylation might be related to the imbalance between HDAC1/2 and KAT8 expression, inhibited its interaction with MFN2, expanding MAM distance and impairing mitochondrial lipid metabolism, and consequently deteriorating hepatic steatosis. Conclusions: The insufficient ALR crotonylation might be a crucial mechanism contributing to the pathogenesis of MASLD. Keeping ALR crotonylation level would be beneficial for the prevention and treatment of MASLD.